Understanding Tourist Satisfaction in Borobudur: The Role of Destination Image, Service Quality, and Sustainability - Hidayah, Atika Nur; Fachrie, Muhammad; Kristianto, Yohanes Ivan Adi; Pratiwi, Ade Shinta (Sekolah Vokasi, Universitas Gadjah Mada, 2025)
This study aims to examine the effects of destination image, service quality, and sustainable practices on tourist satisfaction in Borobudur’s tourism villages. Using a quantitative approach, data were collected from 100 domestic tourists through structured questionnaires. The results of multiple linear regression analysis show that destination image and service quality have a significant and positive influence on tourist satisfaction, with service quality having the strongest effect. In contrast, sustainable practices were found to have no significant effect, suggesting a possible disconnect between sustainability efforts and tourist awareness or expectations. These findings highlight the importance of strengthening service standards and enhancing the perceived image of tourism villages while making sustainability efforts more visible and experiential. The study contributes to both theoretical understanding and practical strategies for community-based tourism development.